Analisis kemampuan pemahaman matematis pada mata kuliah kalkulus peubah banyak - Wahyuni, Arie; Hidayati, Destia Wahyu (Universitas Muhammadiyah Purworejo, 2020)
This study aims to determine the ability of students’ mathematical understanding in the multi-variable calculus course. The method used in this study is a test. This test will be used to determine students’ mathematical comprehension abilities in the multivariable calculus course. The results of this study concluded that 3 students scored 50-60, 4 students scored 60-70, 6 students scored 70-80. There are several factors that cause student scores to not get perfect scores, namely in the learning process there is a need for an attractive learning model, the need for technology, etc.